Allelopathic effects of invasive weed species Abutilon theophrasti Medik., Ambrosia artemisiifolia L., Datura stramonium L. and Xanthium strumarium L. on tomato - Radivojević, Ljiljana; Sarić-Krsmanović, Marija; Gajić Umiljendić, Jelena; Šantrić, Ljiljana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
Abutilon theophrasti Medik, Ambrosia artemisiifolia L., Datura stramonium L. and Xanthiumstrumarium L. are four well-known invasive weed species that are widespread in manycrops. Laboratory experiments were conducted to evaluate the allelopathic effects ofdecomposition products of these four invasive weeds on seed germination and earlyseedling growth of tomato. The results of the study showed that decomposition productsobtained from A. theophrasti, A. artemisiifolia, D. stramonium and X. strumarium had differentallelopathic impacts on germination and seedling growth of tomato. The degree ofinhibition or stimulation depended on weed species and type of decomposition product.Root decomposition products of all species except X. strumarium decreased the earlygrowth of tomato (2-37%). X. strumarium had only stimulating effect on early growth oftomato (1-86%). Also, the results showed that leaves of the other three invasive weedspecies had stimulating effects on early growth of tomato (1-53%). Hence, the allelopathicpotential of X. strumarium, as well as the leaf decomposition products of the other threeinvasive weed species could be used to develop an appropriate technology to improvetomato production.
Keywords: invasive weeds; allelopathy; tomato; germination; seedlings